Genome‐scale data reveal that endemic Poecilia populations from small sulphidic springs display no evidence of inbreeding. Issue 19 (24th August 2017) - Brown, Anthony P.; Greenway, Ryan; Morgan, Samuel; Quackenbush, Corey R.; Giordani, Luca; Arias‐Rodriguez, Lenin; Tobler, Michael; Kelley, Joanna L.
Abstract: Populations with limited ranges can be highly vulnerable to changes in their environment and are, thus, of high conservation concern. Populations that experience human‐induced range reductions are often highly inbred and lack genetic diversity, but it is unknown whether this is also the case for populations with naturally small ranges. The fishes Poecilia sulphuraria (listed as critically endangered) and Poecilia thermalis, which are endemic to small hydrogen sulphide‐rich springs in southern Mexico, are examples of such populations with inherently small habitats. We used geometric morphometrics and population genetics to quantify phenotypic and genetic variation within and among two populations of P. sulphuraria and one population of P. thermalis . Principal component analyses revealed phenotypic and genetic differences among the populations. Evidence for inbreeding was low compared to populations that have undergone habitat reduction. The genetic data were also used to infer the demographic history of these populations to obtain estimates for effective population sizes and migration rates. Effective population sizes were large given the small habitats of these populations. Our results imply that these three endemic extremophile populations should each be considered separately for conservation purposes. Additionally, this study suggests that populations in naturally small habitats may have lower rates of inbreeding and higher genetic diversity than expected, and therefore may be better equipped to handle environmental perturbations than anticipated. We caution, however, that the inferred lack of inbreeding and the large effective population sizes could potentially be a result of colonization by genetically diverse ancestors.